Smoking and related factors of the social environment among adolescents in the Republic of Karelia, Russia in 1995 and 2004 - Rogacheva, Anastasiya; Laatikainen, Tiina; Patja, Kristiina; Paavola, Meri; Tossavainen, Kerttu; Vartiainen, Erkki (The European Journal of Public Health, 2008)
Background : To investigate changes in smoking prevalence associated with social factors and existing health policies among adolescents in Russia from 1995 to 2004. Methods: In 1995 and 2004 a confidential questionnaire was distributed to every 9th grade student of all 10 comprehensive schools of the Pitkäranta in Republic of Karelia, Russia. In 1995, 385 children participated in the survey (response rate 95%) and 395 children (response rate 85%) in 2004. Results: Twenty-nine percent of boys smoked daily in 1995 and 31% in 2004. Daily smoking doubled from 7% to 15% for girls. Smoking in the schoolyard increased among girls. The proportion of girls who reported smoking at home with their parents’ knowledge increased. Both genders cited the ease of purchasing tobacco as a minor. Knowledge about the fast development of tobacco addiction increased statistically significantly among boys. Fewer numbers of respondents of either gender thought that young smokers look ‘cool’ and more grown up. Having a best friend who smoked was the strongest predictor for smoking for both genders. Conclusion : Smoking has increased among girls. Social environment is a predisposing factor. Anti-smoking legislation was implemented weakly. Minors purchase tobacco relatively easily. Knowledge about tobacco's harmfulness has somewhat increased but is not sufficient to deter starting smoking, especially among non-smoking girls. Adequate education of adolescents on the hazards of tobacco consumption is needed, accompanied by a more determined enforcement of health policies. The potent influence of peers should be considered when planning preventive interventions.